La puissance satanique de la mimesis chez René Girard (Itinera, 2024)
Since 1961, René Girard has built a complete fundamental anthropology based on a single intuition: the theory of mimetic desire. While philosophical modernity had made us believe that the fundamental category of the subject was autonomy, Girard reminds us on the contrary that we are mimetic animals. However, mimesis is paradoxical. It is because we all have a desire for differentiation that we are condemned to imitate one another. In doing so, by rethinking mimesis and taking it out of its simple traditional representational field in which it was often confined, the author shows how it reveals all its ambivalence, both pacifying and violent, and allows Girard to place it not only at the heart of humanity but also at the center of the process of hominization.
Keywords: Scapegoating, Difference, Reciprocity, Violence